The Analysis of Blog Use as A Marketing Communication Tool by the Selected Target Group in the Conditions of the Slovak Market - FEDORKO, Richard; BAČÍK, Radovan; KOT, Sebastian; KAKALEJČÍK, Lukáš (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
Blogs are social media that are owned by companies. Therefore, online identity building via blogs is important from the long term point of view. Blogs allow to distribute more complex content following the needs of potential buyers to obtain information on companies’ products. The aim of this article is to examine the use of blogs during the purchasing process. By evaluating the results of the questionnaire we arrived to the conclusion that more than half of the respondents are regular monthly visitors of blogs. Moreover, it was found that blogs help users in different parts of the buying process including the purchase itself. By testing the hypothesis we demonstrated statistically significant relationship between blog visits frequency and purchases made based on blogs.
Keywords: blog; social media; online marketing; content; copyright